EXPLORING SENIOR HIGH SCHOOL STUDENTS’ MISCONCEPTIONS IN NEWTONIAN MECHANICS: A QUALITATIVE INVESTIGATION - Rodika Utama; Okimustava; Moh. Toifur; Nurlailah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Newtonian mechanics remains a fundamental yet conceptually challenging domain for high school students. Numerous studies have shown that students consistently hold alternative conceptions that contradict scientific understanding, particularly in relation to Newton’s laws of motion. This study aimed to explore senior high school students’ misconceptions in Newtonian mechanics through a qualitative investigation. Data were collected from 28 Grade 11 students in an Indonesian high school using open-ended diagnostic tests, semi-structured interviews, and classroom observations. Thematic coding identified four major categories of misconceptions: inertia, force–motion relationships, action–reaction interactions, and free-body diagram representations. Among these, misconceptions of Newton’s third law were the most dominant, with the majority of students believing that the object with greater mass exerts a greater force during interaction. Inertia misconceptions, such as the belief that motion requires continuous force, were also widespread. The findings confirm that students’ misconceptions are robust cognitive frameworks reinforced by everyday experiences and traditional teaching practices. Pedagogically, the results highlight the importance of incorporating inquiry-based learning, multiple representations, and cognitive conflict strategies to promote conceptual change. This study contributes to the literature on physics education by providing context-specific insights into persistent misconceptions in Newtonian mechanics and suggesting implications for more effective teaching practices.